ICFHR 2012 Competition on Handwritten Document Image Binarization (H-DIBCO 2012) - Pratikakis, I.; Gatos, B.; Ntirogiannis, K. (2012 International Conference on Frontiers in Handwriting Recognition, 2012)
H-DIBCO 2012 is the International Document Image Binarization Competition which is dedicated to handwritten document images organized in conjunction with ICFHR 2012 conference. The objective of the contest is to identify current advances in handwritten document image binarization using meaningful evaluation performance measures. This paper reports on the contest details including the evaluation measures used as well as the performance of the 24 submitted methods along with a short description of each method.